Improving subsidiaries' innovation through knowledge inflows from headquarters and peer subsidiaries - Crespo, Cátia Fernandes (2021)
This study develops a conceptual model that compares the intensity of the impact of knowledge inflows from peer subsidiaries and from the headquarters in the promotion of a focal subsidiary's innovation activities, moderated by socialization mechanisms and national cultural distance. The authors test hypotheses with a dataset comprised of survey data from 202 multinational corporations (MNC) Portuguese subsidiaries. The results indicate that although knowledge inflows from both the headquarters and peer subsidiaries promote the focal subsidiary's innovations capabilities, headquarters' knowledge transfer is a superior and more efficient source of knowledge in the promotion of a subsidiary's new product development. Moreover, socialization mechanisms, both lateral and vertical integrating mechanisms, act as critical instruments that facilitate the incorporation of the incoming knowledge flows into innovation. This study extends the literature on knowledge transfer in MNCs by exploring how two sources of knowledge transfer, the headquarters and peer subsidiaries, influence a focal subsidiary's new product development, investigating socialization mechanisms and national cultural distance moderating effects.